Development Of A Low Cost Fiber Optic Tsunami Monitoring System. - Rehman, Mahfoozur; Arshad, M.Rizal; Aish, Aamir Abul (2008)
Due to the large scale devastation done by Tsunami, in nearly 22 different countries, in December 2004, interest in the development of tsunami warning system is increasing very rapidly in the developing countries as they have large amount of funds available for this purpose.